A process for desulfurization of coking benzene by a two-step method with reuse of sorbent/thiophene and its key procedures. Issue 5 (12th May 2015) - Liao, Junjie; Wang, Yashan; Chang, Liping; Bao, Weiren
<x xml:space="preserve">Abstract</x> Pure benzene is an important chemical feedstock, and coking benzene is one of its sources.